Presentation of a Mobile Testing Device for the Inspection of Micropiles of Rockfall Protection Nets in Alpine Terrain - Edler, Jörg; Rebhan, Matthias; Troyer, Emanuel (International Conference Fluid Power 2025: Conference Proceedings, 2025)
The protection of structural facilities in alpine regions from natural hazards–particularly rockfalls–is becoming increasingly important due to global warming. While installing protection systems such as rockfall nets is an important first step, these systems require long-term maintenance and regular inspection to ensure functionality. Although inspection of the nets themselves is often feasible in alpine terrain, inspection of the ground anchors has not been possible until now. This challenge motivated the development of a hydraulically powered, mobile testing device specifically designed to evaluate the ground anchors of rockfall nets in alpine areas. The hydraulic concept enables the required forces to be generated within a short time, while the compact design allows the device to be carried through difficult terrain by just two people.